Isolation of amplified DNA sequences from IMR-32 human neuroblastoma cells: facilitation by fluorescence-activated flow sorting of metaphase chromosomes. - Kanda, N (1983)
Human neuroblastoma IMR-32 cells have large homogeneously staining regions (HSRs), primarily in the short arms of chromosome 1. We have constructed a recombinant phage library that is enriched for DNA present in the HSR of this chromosome by using fluorescence-activated flow sorting for initial chromosome purification. Eleven distinct cloned DNA segments were identified that showed significantly greater hybridization to IMR-32 genomic DNA, detected by Southern blotting, than to normal human genomic DNA. These sequences have also been localized to the HSR of chromosome 1 by in situ hybridization. Based on an approximate 50-fold sequence amplification for each cloned segment and a total HSR size of 150,000 kilobases, the amplified unit in the HSR is estimated to be 3,000 kilobases. Sequences homologous to all cloned HSR DNA segments were mapped to human chromosome 2 by using human-mouse hybrid cells. Further work using in situ hybridization demonstrated that cloned HSR segments were localized in the short arm of chromosome 2 in both normal and IMR-32 cells. Thus, the amplification of these sequences in IMR-32 cells may have involved transposition from chromosome 2 to chromosome I.